2016
DOI: 10.4103/0019-5545.196720
|View full text |Cite
|
Sign up to set email alerts
|

Personality disorders and its association with anxiety and depression among patients of severe acne: A cross-sectional study from Eastern India

Abstract: Background:In many patients, emotional stress may exacerbate acne. Psychological problems such as social phobias, low self-esteem, or depression may also occur as a result of acne. The presence of acne may have some negative effect on the quality of life, self-esteem, and mood of the affected patients. While some studies have been undertaken about anxiety, depression, and personality patterns in patients with acne, only a few studies have been done to identify specific personality disorders in patients with ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 24 publications
2
27
0
1
Order By: Relevance
“…When it came to Grade 4 acne patients 83% had moderate anxiety, whereas moderate to severe anxiety was seen among one patient in Grade 3 &4 each. Similar results were observed by Sarkar et al 16 and Purvis et al 17 where there was a positive correlation between acne grades and anxiety scores.…”
Section: And Javed Et Alsupporting
confidence: 89%
See 1 more Smart Citation
“…When it came to Grade 4 acne patients 83% had moderate anxiety, whereas moderate to severe anxiety was seen among one patient in Grade 3 &4 each. Similar results were observed by Sarkar et al 16 and Purvis et al 17 where there was a positive correlation between acne grades and anxiety scores.…”
Section: And Javed Et Alsupporting
confidence: 89%
“…None of our patients reported severe depression. The severity of the acne directly correlated with depression scores in the patients, similar results were observed by Sarker et al 16 Purvis et al 17 & Ulsu et al 18 While it is well known that acne and other skin conditions are known to cause psychological distress and leads to increased psychiatric morbidity, Bondade et al 19 found that 40% of the acne population showed comorbid psychiatric illness. Contrary to majority of the findings, some studies have reported that acne doesn't have any significant effect on the psyche of the individual, Atkan et al 20 conducted a study on 2657 acne patients, he observed that there was no correlation between acne severity & HAM-D & HAM-A scores.…”
Section: And Javed Et Alsupporting
confidence: 75%
“…The mechanisms for the increased admission rates for MH disorders in patients with acne or rosacea are unknown. Acne and rosacea have been found to be associated with increased rates of personality disorders and/or mood disorders, including depression and anxiety . It may be that more severe acne and rosacea are associated with severe MH symptoms, warranting clinical hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Acne and rosacea have been found to be associated with increased rates of personality disorders and/or mood disorders, including depression and anxiety. [19][20][21] It may be that more severe acne and rosacea are associated with severe MH symptoms, warranting clinical hospitalization. A complex interaction of cutaneous and gut microbiome has been proposed to have an impact on acne severity and potentially influence systemic inflammation, oxidative stress, glycaemic control and ultimately MH symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Akne de depresyon ve kişilik bozukluğu gibi pek çok hastalığı tetiklemektedir. Sonuçta kısır döngü unutkanlık, hafızayı düzgün kullanamama gibi patolojik durumlara neden olabilmektedir (7).…”
Section: Introductionunclassified